Effect of prednisone and relation on length of tooth movement in rats (Rattus norvegicus) - Ruiz, Eliberto (2014)
This experimental study was to evaluate the effect of prednisone on the ratio of the length of tooth movement in rats (Rattus norvegicus). The evaluation of this relationship was performed in 20 male Wistar rats 12 weeks of age, weighing 225 ± 25 g, to which adapted a orthodontic breaker in their upper central incisors, were then randomly divided into two groups: control (physiological saline to 2 mL/kg) and experimental (prednisone 20 mg/kg ip), the treatment began five days before placement of the device and then to the first, third and fifth day. With a gauge, was measured the interincisisor distance to finish placing the device, as so as to the first, third, fifth and seventh day. On the 1st day of testing, the control group and the experimental group had a interincisiva distance 1,13 ± 0,18 mm and 0,24 ± 0,09 mm and the 7th day was 1,76 ± 0,14 mm and 1,56 ± 0,20 mm, respectively, with significant differences in the first and seventh days (p<0,05). It’s conclude that prednisone significantly reduces tooth movement in rats.